(untitled) (Biological Sciences - PJSIR, 2002)
The effect of seed of sweet clover (!vfelilotus indica L.) was eval uated alone or in combination wi th NaCl on the germination and seedling growth of rice. As compared to control, there was significant inhibi tory effect on germi nation and the maximum reduction o[ 25% was recorded when 0.4% NaCl and weed seed were applied together. The growth of both shoot and root significantly decreased under NaC l as wel l as with the placement of weed seed. Root growth was affected more than shoot. The effect of NaCl was accentuated in the presence of weed seed. Reduction in shoot length was 40 and 45% wi th weed seed alone and al 0.2% NaCl, respectively. The correspondi n g figures for root were 95% and 94° o, respectively. Tt wa s concl uded lhal weed seed or sweet clover i n co111 bi11alio11 with NaCl had signiftc,1nl inhi bi to,y effects on germi nation and seedling growth of rice.